The effects of industry 4.0 on productivity: A scientific mapping study - Özköse, Hakan; Güney, Gül; Özköse, Hakan; Güney, Gül (Elsevier Sci Ltd, 2023)
Industry 4.0 is a prevailing topic in contemporary discourse, and the volume of scholarly research in this domain is rapidly expanding. Within the last decade alone, the Web of Science database has yielded a corpus of nearly 38,000 publications. Productivity, as a multifaceted concept, is profoundly influenced by various domains, with Industry 4.0 exerting a particularly noteworthy impact on industrial sectors. In this investigation, a rigorous scientific mapping endeavor has been undertaken to examine the interplay between Industry 4.0 and productivity. To this end, bibliometric data encompassing 523 articles and 63 review articles on the subjects of Productivity and Industry 4.0 were extracted from the Web of Science database. These 586 articles were subsequently subjected to comprehensive analysis, employing the SciMAT program to facilitate both bibliometric assessments and content analysis. The bibliometric evaluation encompasses the evolution of publication output, identification of influential authors and journals within the field, scrutiny of highly cited publications, and an examination of the most frequently referenced works. The content analysis stage harnesses Strategic Diagrams, Thematic Networks, and Evolutionary Maps to discern overarching themes, associated terminologies, and their temporal evolution. The resulting findings are meticulously interpreted and explicated for each individual theme, affording nuanced insights into the intricate relationship between Industry 4.0 and productivity.
Keywords: Industry 4.0; Productivity; Bibliometric Analysis; Scientific Mapping; Content Analysis